Child labour, school attendance and orphaned children in the Democratic Republic of the Congo - Isidore Murhi Mihigo; Guillaume Vermeylen; Deogratias Bugandwa Munguakonkwa (Discover Global Society, 2024)
Abstract This article contributes to the stock of scientific knowledge by showing the effect of orphan status on child labour and school attendance in the Democratic Republic of the Congo (DRC). While the abolition of child labour is undeniably one of the major tasks assigned to the International Labour Organization (ILO) when it was founded, child labour remains a severe problem worldwide. In many parts of the world, especially in developing countries, children do not have access to school. Instead of ending up in school, millions of children are forced to engage in child labour in income-generating and non-income-generating activities. Little researchers have yet made it possible to obtain simultaneous information on child labour, school attendance and orphaned children. This paper describes the research that tries to make such a connection. Data used is from the out-of-school children and adolescents (OOSC-DRC-2012) survey organised by the Ministry of Primary, secondary and Vocational Education. Using a bivariate probit econometric model and testing the endogeneity with an instrumental variables approach, funding of the analysis supports the assumption of a significant negative relationship between child labour and school attendance. The result shows also that being orphaned reduces a child's likelihood of school attendance and increases the probability of entering the labour market. It is underlined that most children are present in non-income-generating than income-generating activities.